Phonetic Imitation of Vowel Duration in L2 Speech - Zając, Magdalena (Research in Language, 2013)
This paper reports the results of a pilot study concerned with phonetic imitation in the speech of Polish learners of English. The purpose of the study was to investigate whether native speakers of Polish imitate the length of English vowels and to determine whether the extent of phonetic imitation may be influenced by the model talker being a native or a non-native speaker of English. The participants were asked to perform an auditory naming task in which they indentified objects and actions presented on a set of photos twice, with and without the imitation task. The imitation task was further sub-divided depending on the model talker being a native or non-native speaker of English (a native Southern British English speaker and a native Polish speaker fluent in English). As the aim was to investigate the variability in durational characteristics of English vowels, the series of front vowels /æ e ɪ iː/ were analysed in the shortening and lengthening b_t vs. b_d contexts. The results of the study show that the participants imitated the length of the investigated vowels as a result of exposure to the two model talkers. The data suggest that the degree of imitation was mediated both by linguistic and social factors and that the direction of convergence might have been affected by the participants’ attitude toward L2 pronunciation.